Impact of Plant Peptides on Symbiotic Nodule Development and Functioning - Kereszt, Attila; Mergaert, Peter; Montiel, Jesús; Endre, Gabriella; Kondorosi, Éva (Frontiers in Plant Science, 2018)
Ribosomally synthesized peptides have wide ranges of functions in plants being, for example, signal molecules, transporters, alkaloids, or antimicrobial agents. Legumes are an unprecedented rich source of peptides, which are used to control the symbiosis of these plants with the nitrogen-fixing Rhizobium bacteria. Here, we discuss the function and the evolution of these peptides playing an important role in the formation or functioning of the symbiotic organs, the root nodules. We distinguish peptides that can be either cell-autonomous or secreted short-range or long-range signals, carrying messages in or between plant cells or that can act as effectors interacting with the symbiotic bacteria. Peptides are further classified according to the stage of the symbiotic process where they act. Several peptide classes, including RALF, DLV, ENOD40, and others, control Rhizobium infection and the initiation of cell divisions and the formation of nodule primordia. CLE and CEP peptides are implicated in systemic and local control of nodule initiation during autoregulation of nodulation and in response to the nutritional demands of the plant. Still other peptides act at later stages of the symbiosis. The PSK peptide is thought to be involved in the suppression of immunity in nodules and the nodule-specific cysteine-rich, GRP, and SNARP (LEED..PEED) peptide families are essential in the functioning of the nitrogen fixing root nodules. The NCRs and possibly also the GRP and SNARPs are targeted to the endosymbionts and play essential roles in the terminal differentiation of these bacteria.